(untitled) (Biological Sciences - PJSIR, 2002)
The mechanical and rheological properties of natural rubber composites activated with the conventional saturated ZnO/ stearic acid pair have been studied extensively (Bristow 1986; Elliot 1986; Barker 1987). The mechanical and rheological properties of natural rubber composites activated with ZnO/ unsaturated carbox’)’lic acid have been reported (Bristow 1987). The effect of cure temperature on the mechanical prop erties of natural rubber activated wit ZnO/saturated carbOll.’)’ lic acid has also been reported (Barker 1987; Adeosun et al 1998). The them10dynamics of stretching and the thermal con ductivity of the systems ZnOJsaturated carbox’)’lic acid have however not been given much attention as their mechanical and rheological properties . In this work, the thermal conduc tivities and the thermodynamic parameters of these systems have been exami ned alongside their mechanical and rheo logical properties.